Heralds of the good news : Isaiah and Paul "in concert" in the letter to the Romans - Wagner, J. Ross. (Novum Testamentum, Supplements, 2002)
In this text-critical, literary, and theological investigation of Paul's interpretation of Isaiah in Romans, it is argued that Paul's citations and allusions evince sustained and careful attention to significant portions of Isaiah, in concert with other scriptural voices. Through a radical rereading of Isaiah, Paul appropriates these prophetic oracles as prefigurations of his own mission to Gentiles while simultaneously appealing to Isaiah as a witness to God's continuing fidelity to Israel. The book examines each of Paul's citations and allusions to Isaiah, situating them both within the milieu of early Jewish interpretive practices and within the context of Paul's unfolding argument in Romans. This volume contributes to the current debate about early Christian interpretation of scripture by tracing the complex and dynamic interrelationship in Paul's letter of Scripture, theology, and mission. This publication has also been published in paperback, please click here for details.